2010
DOI: 10.4314/jasem.v5i1.54950
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Of Diabetes Mellitus Among Nigerians In Port Harcourt Correlates With Socio-Economic Status

Abstract: Random blood glucose analysis by the use of the Trinder's method was carried out to determine the prevalence of diabetes mellitus among Nigerians in Port Harcourt. The study population were randomly selected and classified into two socio-economic status as high or low based on affluent diet, occupation, income and access to medical care. The mean blood glucose concentration for the high socio-economic group -staff of the oil industries was 7.42 ±0.25mmol/L and significantly higher (P < 0.001) than that for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 4 publications
(1 reference statement)
8
27
0
Order By: Relevance
“…Poor health seeking behaviour results in late presentation and is a possible reason why majority of patients in these setting present with complications [14]. For diabetic children, it is possible that some of the affected children succumbed to the illness at home out of parental ignorance and high cost of orthodox medical care.…”
Section: Ignorancementioning
confidence: 99%
See 2 more Smart Citations
“…Poor health seeking behaviour results in late presentation and is a possible reason why majority of patients in these setting present with complications [14]. For diabetic children, it is possible that some of the affected children succumbed to the illness at home out of parental ignorance and high cost of orthodox medical care.…”
Section: Ignorancementioning
confidence: 99%
“…From various African studies, clinical diabetic nephropathy in Sudan 11.6% [69], 19% in 1971 in Nigeria [70], 46% in Kenya [71] and 6% in Ethiopia [72]. The exact cause of diabetic induced complications are not fully understood, the underlying factor that appears to make those with diabetes more prone to many health problems is prolonged and frequently elevation of blood sugar [14]. Diabetes mellitus is a complex metabolic disease that can have devastating effects on multiple organs in the body.…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence of Diabetes Mellitus among Nigerians in Port-Harcourt correlates with socioeconomic status was studied by Nwafor and Owhoji (2001). They found that, the prevalence was as high as 23.4% among the high socio-economic group and 16% among the low socio-economic group.…”
Section: Introductionmentioning
confidence: 99%
“…The literature relating to the prevalence of Diabetes in Nigeria is scarce (Nwafor and Owhoji, 2001). So far Diabetes is a well known major public health problem worldwide, there is therefore the growing tendency that every effort should be directed towards actively looking for the prevalence of Diabetes Mellitus in the Nigerian population.…”
Section: Introductionmentioning
confidence: 99%